The densification behavior of flash sintered BaTiO3. (September 2020) - Ren, Ke; Huang, Sisi; Cao, Yejie; Shao, Gang; Wang, Yiguang
Abstract: Herein, we report the densification behavior of a typical electric ceramic, barium titanate (BaTiO3 ), and highlight the role of oxygen vacancies in rapid densification of BaTiO3 during flash sintering. The activation energies of flash- and conventional-densification processes are compared to reveal that the initiation of flash sintering is triggered by the accumulation of generated oxygen vacancies under the electric field. Furthermore, the densification kinetics of BaTiO3 and X-ray photoelectron spectroscopy of flash-sintered BaTiO3 infer that the ultrafast densification during the flash-sintering stage is dominated by the migration of electric field-generated defects coupled with defect-annihilation by take-in oxygen from the environment. Graphical Abstract: Image, graphical abstract